Love, Compassion, and Sustainability Accounting: An Islamic Values-Based Framework for Ethical and Spiritual Sustainability Reporting - Ika Agustina; Elvira Sitna Hajar; Tetty Nur Intan Rifia; Azizatul Munawaroh; Rindu Ferdina Lestari; Rahmat Irawan (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study proposes a conceptual framework for sustainability accounting grounded in Islamic values of love and compassion (mawaddah and rahmah). Employing a qualitative library research methodology, the study synthesizes classical Islamic sources—the Quran, Hadith, and juristic principles—alongside contemporary sustainability literature encompassing GRI standards and ESG frameworks. The analysis identifies five foundational elements of an Islamic sustainability accounting framework: (1) accountability toward all of creation (rahmah); (2) balance across economic, social, and environmental dimensions (tawazun); (3) intergenerational compassion (maslahah and amanah); (4) transparency as an expression of love and honesty (sidq); and (5) ethical consumption and production (qana'ah and itqan). The proposed framework is not merely normative but offers actionable sustainability reporting indicators applicable across diverse organizational contexts. This study contributes an epistemological dimension to Islamic accounting theory by integrating spiritual and ethical values into sustainability reporting practice, thereby enriching the broader discourse on accountable, inclusive, and equitable sustainable development.